On the question of optimizing the quality of energy in city electric network - Hovorov, Pylyp; Hovorov, Vladlen; Kindinova, Anastasiia (Національний технічний університет "Харківський політехнічний інститут", 2022)
As is well known, ensuring the energy quality indicators set by the State Technical Service of Ukraine in electrical networks is an extremely important task. The heterogeneity of load schedules of consumers of urban electric networks in combination with the variety of their operating modes, phase differences, non-linearity and high speed of parameter changes led to the fact that asymmetry, non-sinusoidal, voltage deviations and fluctuations in the networks became permanent factors that significantly reduce the quality of the networks and consumers connected to them. In addition, studies of the power factor in urban electrical networks indicate a low level of reactive power compensation in them. This is due to the high value of voltage and power losses in networks, the technical need and economic feasibility of compensation of reactive power in them. Research conducted at O. M. Beketov Kharkiv National University of Urban Economy, testify to the fact that the main strategic directions for improving the quality of energy in urban electric networks are voltage regulation, taking into account the comprehensive solution of the issues of improving the quality of energy and compensation of reactive power. At the same time, the technical solution to the problem is on the way of multi-level correction of quality indicators by using additional multifunctional devices, the most important place among which is occupied by devices made on the basis of thyristor-controlled voltage transformers. The paper presents the results of this study. It is also determined that in combination with the automation of the process of managing multifunctional devices, the use of multifunctional converters as a whole allows solving the issue of optimizing the operation modes of city power supply systems. The application of research results in general allows solving the issue of energy quality optimization in urban electrical networks.

Як відомо, забезпечення встановлених ДСТУ показників якості енергії в електричних мережах є надважливим завданням. Неоднорідність графіків навантаження споживачів міських електричних мереж у поєднанні з розмаїттям їх режимів роботи, пофазною відмінністю, нелінійністю та високою швидкістю зміни параметрів зумовили те, що несиметрія, несинусоїдність, відхилення та коливання напруги в мережах стали постійно діючими факторами, що істотно знижують якість роботи мереж та підключених до них споживачів. Крім того, дослідження коефіцієнта потужності у міських електричних мережах вказують на низький рівень компенсації реактивної потужності в них. Цим зумовлюється високе значення втрат напруги та потужності в мережах, технічна потреба та економічна доцільність компенсації реактивної потужності в них. Дослідження, проведені у ХНУМГ ім. О.М. Бекетова, свідчать про те, що основними стратегічними напрямками підвищення якості енергії у міських електричних мережах є регулювання напруги з урахуванням комплексного вирішення питань підвищення якості енергії та компенсації реактивної потужності. При цьому технічне вирішення проблеми знаходиться на шляху багаторівневої корекції показників якості шляхом застосування додаткових пристроїв багатофункціонального призначення, найважливіше місце серед яких займають пристрої, виконані на базі вольтододавальних трансформаторів з тиристорним керуванням. У роботі представлено результати цього дослідження. Також визначено, що у поєднанні з автоматизацією процесу управління багатофункціональними пристроями застосування багатофункціональних перетворювачів в цілому дозволяє вирішувати питання оптимізації режимів роботи систем електропостачання міст. Застосування результатів дослідження загалом дозволяє вирішувати питання оптимізації якості енергії у міських електричних мережах.
До питання про оптимізацію якості енергії у міських електричних мережах
Keywords: optimization; electrical energy; quality of electrical energy; urban electrical networks; voltage regulation; compensaton of reactive power; оптимізація; електрична енергія; якість електричної енергії; міські електричні мережі; регулювання напруги; компенсація реактивної потужності